A method to improve water‐holding capacity of beef during freezing‐thawing process using ultrasound treatment. Issue 1 (21st November 2020) - Wang, Xiaodan; Dong, Yanli; Wu, Ruijia; Liu, Dengyong; Hu, Feng; Wang, Cuilian; Wu, Duo
Abstract: The effect of ultrasound treatment on water‐holding capacity (WHC) of beef during freezing‐thawing process was investigated. The results showed that the WHC of beef without ultrasound was 0.69 after one freezing–thawing process. In different stages of freezing and thawing (before freezing, during freezing, during thawing, and after thawing), the application of ultrasound (400 w, 45 kHz) could improve the WHC quality of beef: the WHC was improved most during thawing, which could reach 0.78. And then, ultrasound treatment could reduce hardness but improve springiness ( p  < .05) and pH value of beef in freezing–thawing process. Scanning electron microscope images showed that the lacuna of myofibrils increased, which indicated that the ultrasound could help to improve the WHC. Based on the results obtained, ultrasound treatment may be recommended as a useful means to improve the WHC of beef during freezing–thawing process. Practical applications: In the process of food production, raw meat may undergo repeated freezing–thawing, which would affect the quality of meat. Ultrasound, as a new technology, was used in this study. This study showed that ultrasound could help to improve the WHC of beef during freezing–thawing process. Therefore, it is reasonable to conclude that ultrasound can be used as an effective technology to improve the quality of beef during freezing–thawing process.